Re: Gen - web-based resume generator with content recommender for it job field / Nurul Syahmina Mohd Khairuddin … [et al.] - Mohd Khairuddin, Nurul Syahmina; Ahmadon, Fadzlin; Hashim, Madihah Hannani; Mohd Vauxhall, Nur Ain Emylia (Faculty of Computer and Mathematical Sciences, 2022)
Resume creation for job application purposes is important. First and foremost, recruiters receive a first impression of your profile when they go over résumé. In reality, most recruiters look over a résumé for no more than 6 seconds on average. To provide valuable inputs into professionally formatted résumé can stand-out as per desired job requirements. Therefore, the purpose of this system is to generate résumé with content recommendations specifically for the IT job field. Waterfall model has been chosen as the methodology because the project is being developed step by step from requirement gathering and analysis to testing and evaluation. Content-based recommendation algorithm is implemented into the system as it can recommend the best skill content suitable for a job application. Web-based is the platform chosen for this application to develop on as it is more faster and user-friendly application creation for desktop and mobile devices. Before the project can be used by the user, a functionality testing was done to test whether the system has been developed according to the requirement and to correct any mistakes and flaws that were detected during the testing. As a conclusion, the system has been successfully designed, developed, and tested which marks the achievement of all the project’s objectives.